Maintaining optimal physical activity of patients following cardiac rehabilitation - Anna L. Persiyanova-Dubrova; Marina G. Bubnova; David M. Aronov; Inna F. Matveeva (КардиоСоматика)
Physical activity (PA) is an important component of secondary prevention of cardiovascular diseases. PA has a cardioprotective effect and improves the prognosis. Increased PA is associated with a lower coronary risk and decreased overall mortality in patients with a history of myocardial infarction. However, optimal PA achieved during cardiac rehabilitation gradually decreases afterward. Various strategies, including motivational, are used to maintain patients’ PA after cardiac rehabilitation program. Remote rehabilitation using modern digital technologies is also becoming more popular. This literature review discusses studies of the effectiveness of various measures to improve and maintain PA in cardiac patients, provides theoretical and practical considerations, and identifies topics for further researches.